Clinical Study on the Efficacy of Laparoscopic Hepatectomy and Its Influence on the Expression of Serum VEGF, FGF, and Immune Function. (5th October 2021) - Tang, Zhengyong; Tang, Yi; Liu, Tianqi; Liu, Rongjun; Xie, Shaowei; Xie, Dongyi; Yang, Jianrong; Tang, Yuntian
Abstract : Liver cancer is one of the most common malignant tumors. Partial hepatectomy is the most basic and effective treatment for hepatocellular carcinoma because of its high operative effect and perioperative safety. Open surgery is the most traditional hepatectomy. Although it can completely remove tumor lesions and prolong patient survival, it has disadvantages such as large trauma and long postoperative recovery time. Meanwhile, long-term bed rest can increase the risk of complications such as venous thrombosis and infection. The advantages of laparoscopic partial hepatectomy, such as clear operative field, simple operation, little trauma, light surgical stress, quick postoperative recovery, and low complications, can avoid damage to vital organs, blood vessels, and nerves, which has been widely accepted and recognized in clinical practice.